Epidemiology and antimicrobial resistance of Enterobacteriaceae causing community-acquired urinary tract infections in Tétouan, Morocco (2022–2023) - Laila Farouk; Ayoub Ez-Zari; Lahcen Ouchari; Zine El Abidine Bzazou EL Ouazzani; Zakaria Mennane; Noureddine El Mtili (PLoS ONE, 2026)
Background Urinary tract infections (UTIs) are among the most common community-acquired bacterial infections and Enterobacteriaceae are the leading etiological agents. Rising antimicrobial resistance (AMR) within this family poses major challenges for empirical treatment. This study aimed to describe the species distribution and antimicrobial resistance patterns of uropathogenic Enterobacteriaceae isolated from outpatients in Tétouan, Morocco. Methods A cross-sectional descriptive study was conducted between April 2022 and December 2023 in three medical laboratories. Enterobacteriaceae isolated from urine cultures with significant bacteriuria were identified using the VITEK®2 system. Antimicrobial susceptibility testing was performed according to EUCAST 2021 guidelines. Extended-spectrum β-lactamase (ESBL) production was assessed using the Modified Double Disc Synergy Test (MDDST). Statistical analyses were performed using SPSS version 26, with significance set at p < 0.05. Results A total of 422 Enterobacteriaceae isolates were obtained, predominantly from female patients (74.9%). Escherichia coli was the most frequent species (83.4%), followed by Klebsiella pneumoniae (9.2%). High resistance rates were observed for ampicillin (60.9%) and ticarcillin (56.2%), while resistance to imipenem (1.2%) and ertapenem (0.9%) remained low. ESBL production was detected in 20 isolates (4.7%), with E. coli being the predominant ESBL-producing species (16/20; 80.0%), while K. pneumoniae exhibited a higher species-specific prevalence (4/39; 10.3%). Male patients exhibited significantly higher resistance to several β-lactams, while pediatric patients showed higher resistance to cephalosporins and aminoglycosides. Conclusion Uropathogenic Enterobacteriaceae circulating in the community of Tétouan exhibit substantial resistance to commonly prescribed oral antibiotics, although carbapenems remain highly effective. The moderate prevalence of ESBL-producing strains highlights the need for reinforced antimicrobial stewardship and continuous regional surveillance to guide empirical treatment and limit the spread of resistant pathogens.